Համաներման և ներման իրավական ինստիտուտները Հայաստանի խորհրդային ժամանակաշրջանում պատմաիրավական զարգացման համատեքստում - Խաչիկ Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
Статья посвящена изучению проблем амнистии и помилования в период советской власти в Армении. Рассматриваются историко- правовые особенности этих институтов, а также некоторые вопросы конституционно- правового анализа, проблемы объявления амнистии и применения помилования. The article studies the problem of amnesty and pardon in the period of Soviet power in Armenia. In the article the historical and legal peculiarities of these institutions are considered, as well as some issues of constitutional and legal analysis, problems of amnesty declaration and pardon exercising.
Keywords: Law